California Elected Women's Association for Education and Research Newsletter (1976)
This January 1976 CEWAER Newsletter (California Elected Women's Association for Education and Research) highlights upcoming programs, political activity, and organizational growth. It announces a February 6–7 Oakland conference on Women in the Justice System, co-sponsored with local Status of Women Commissions, addressing controversial policy issues faced by elected officials. The newsletter notes that 1976 could be a strong year for women candidates, listing CEWAER members running for county, state, and congressional offices and encouraging support for viable women candidates. Additional updates include congratulations to members on appointments to public boards and committees, expansion of CEWAER nationally through League of Cities networks, progress on an intern program and survey research, and a reminder to save the date for the May 14–15, 1976 annual meeting in San Jose. The issue concludes with a report from Councilwoman Helen Kennedy on the need to strengthen public school music and performing arts programs through local funding and civic leadership.